Editorial: Multidisciplinary insights into distal tibiofibular joint injuries: an integrative analysis of surgical techniques, rehabilitation protocols, and podiatric interventions - Tedeschi, Roberto; Donati, Danilo (Frontiers in Surgery, 2025)
This editorial explores recent advances in the understanding and treatment of tibiofibular joint disorders, integrating evidence from surgical, conservative, and regenerative approaches. Highlighting both distal and proximal dysfunctions, the contributions within this Research Topic reveal underrecognised biomechanical roles and therapeutic opportunities. From meta-analytical data on ankle instability to novel strategies in paediatric and osteoarthritic care, this collection advocates for anatomy-guided, patient-specific interventions. A structured summary of clinical outcomes and evidence levels is provided to guide future interdisciplinary efforts in orthopaedic and podiatric practice.